One last stop [compact disc, unabridged] - McQuiston, Casey (Macmillan Audio, 2021)
Cynical 23-year old August doesn't believe in much when she moves to New York to finish her degree, despite answering an ad for a roommate placed by a psychic and the numerous coincidences that follow: being in exactly the right place and time to be hired on the spot at a diner, one of her mother's cold case file contacts being in her new neighborhood, and seeing the same beautiful girl on the subway every single day. As she gets caught up in the details of impossible Jane -- subway savior who seems to be displaced in time from the late '70s -- the pieces of August's life seem to fall apart and reassemble in an even better formation... but will the new picture include happiness for her roommates, her diner, her mother, and most importantly, August herself?